Rare bird documentation form for Northern Goshawk at Pleasantville, 1983 - Thornburg, Robert E.et al (1983)
Rare bird documentation form for a Northern Goshawk at Pleasantville in Marion County, IA on January 7, 1983. Epson - sheet feed